An evaluation of chromitiferous layers and their host rocks in the Platreef, on the Turfspruit and Zwartfontein properties: a comparative study with the main Bushveld Complex - Cronje, Louwrens (My University, 2017)
The origin of the Platreef in the northern limb of the Bushveld Igneous Complex remains a topic of debate. Its relationship with that of the PGE-reefs of the Main Bushveld Complex is disputed and there is currently no widely accepted theory available, as both parties have valid arguments. This study involves the stratigraphic, petrographic and chemical investigation of the chromitiferous layers and their hosts, in the Platreef, on both the Turfspruit and Zwartfontein properties. The work in this study has shown that the conventional stratigraphy that defines the upper Critical Zone is not present in the study areas, which lack the sophisticated layering and cycles present in the main complex and generally, rocks are significantly more heterogenous in the Platreef than elsewhere in the Bushveld Complex. A large number of petrographic similarities were identified in the study area, when compared to known textures and morphologies published by previous workers, especially on the Upper Group chromitite layers. The chemistry of the Platreef reflect a more primitive magma responsible for the deposition of these rocks, which is demonstrated through higher Mg contents, and lower Ti, indicating less fractionation when compared to the main Bushveld Complex. It must be stated that the influence of contamination on Mg-rich lithologies may have altered their composition, which could have generated misleading results. Statistically, the results obtained may not be entirely representative of the true chemical character of the entire northern limb, and the opinions and assumptions made are very localised. This study concludes that the upper Critical Zone magma was probably not responsible for the deposition of the Platreef, while rocks were locally altered due to contamination from country rock.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2017
Keywords: Geology--South Africa--Bushveld Complex; Geology, Structural--South Africa--Bushveld Complex; Igneous rocks